Two MarR-Type Repressors Balance Precursor Uptake and Glycine Betaine Synthesis in Bacillus subtilis to Provide Cytoprotection Against Sustained Osmotic Stress - Warmbold, Bianca; Ronzheimer, Stefanie; Freibert, Sven-Andreas; Seubert, Andreas; Hoffmann, Tamara; Bremer, Erhard (Frontiers in Microbiology, 2020)
Bacillus subtilis adjusts to high osmolarity surroundings through the amassing of compatible solutes. It synthesizes the compatible solute glycine betaine from prior imported choline and scavenges many pre-formed osmostress protectants, including glycine betaine, from environmental sources . Choline is imported through the substrate-restricted ABC transporter OpuB and the closely related, but promiscuous, OpuC system, followed by its GbsAB-mediated oxidation to glycine betaine. We have investigated the impact of two MarR-type regulators, GbsR and OpcR, on gbsAB, opuB and opuC expression. Judging by the position of the previously identified OpcR operator in the regulatory regions of opuB and opuC [Lee et al. (2013) Microbiology 159, 2087-2096], and that of the GbsR operator identified in the current study, we found that the closely related GbsR and OpcR repressors use different molecular mechanisms to control transcription. OpcR functions by sterically hindering access of RNA-polymerase to the opuB and opuC promoters, while GbsR operates through a roadblock mechanism to control gbsAB and opuB transcription. Loss of GbsR or OpcR de-represses opuB and opuC transcription, respectively. With respect to the osmotic control of opuB and opuC expression, we found that this environmental cue operates independently of the OpcR and GbsR regulators. When assessed over a wide range of salinities, opuB and opuC exhibit a surprisingly different transcriptional profile. Expression of opuB increases monotonously in response to incrementally increase in salinity, while opuC transcription levels decrease after an initial up-regulation at moderate salinities. Transcription of the gbsR and opcR regulatory genes is up-regulated in response to salt stress, and is also affected through auto-regulatory processes. The opuB and opuC operons have evolved through a gene duplication event. However, evolution has shaped their mode of genetic regulation, their osmotic-stress dependent transcriptional profile, and the substrate specificity of the OpuB and OpuC ABC transporters in a distinctive fashion.